A new calibration of the albedo-polarization relation for the asteroids - Cellino, A. (2012)
We present a new calibration of the geometric albedo versus linear polarization relation for the asteroids. We use the classical relation logpv=C1logh+C2, where p V is the geometric albedo and h is the slope of the phase-polarization curve. We have obtained new values for the C 1 and C 2 coefficients and their nominal uncertainties, by means of dedicated polarimetric observations of a number of asteroids for which the albedo is supposed to be known with good accuracy [Shevchenko and Tedesco. Icarus 2006;184:211-220]. The new calibration proposed in this paper represents the state of the art based on currently available data. However, the uncertainties on the derived calibration coefficients are still not negligible, and we suggest that alternative forms of the albedo-polarization relation should be explored in the future, possibly based on a bigger data set of polarimetric measurements.